(untitled) (Nigerian Journal of Physiological Sciences, 2025)
This study evaluated gastroprotective biochemicals in Wistar rats exposed to both Bisphenol A and either Garcinia kola or its biflavonoid, kolaviron. Fifty-six rats (140-160g) divided into 7 groups (n=8), and treated orally for 28 days as follows; Group I was the control (distilled water, 1.5mL/kg) while group II (vehicle control) received corn oil (1.5mL/kg), groups III-V were exposed to BPA (50mg/kg) only and treated with distilled water (1.5mL/kg), Garcinia kola (200mg/kg) and kolaviron (200mg/kg), respectively. Animals in groups VI and VII received Garcinia kola (200mg/kg) and kolaviron (200mg/kg) only, respectively. Thereafter and under anaesthesia, the stomach was dissected out, estimated for mucin (n=3), homogenized (n=5), centrifuged, and the clear supernatant obtained was analyzed for malondialdehyde, superoxide dismutase, catalase, reduced glutathione, glutathione S-transferase, nitrites, myeloperoxidase, interleukin-6 and tumor necrosis factor-α, respectively.Gastroprotective biochemicals were significantly (p<0.05) reduced in animals exposed to BPA while values in animals exposed both BPA and either Garcinia kola or kolaviron were elevated. Exposure to Garcinia kola and kolaviron alone also showed a potentiation of gastric antioxidant and anti-inflammatory activities. This study shows that Garcinia kola and especially its biflavonoid, kolaviron, protects the gastric mucosa against Bisphenol A induced impairment by potentiating gastroprotective biochemicals in male Wistar rats.